الثورة الصناعية الرابعة كآلية لدافع وتعزيز التنويع الاقتصادي من اجل تنمية مستدامة شاملة في المغرب العربي - حميتي, نور الهدى; حملاوي, سكينة (جامعة الوادي - University of Eloued, 2023)
The study aims to demonstrate the importance of the Fourth Industrial Revolution and its results in economic diversification. And highlighting the role of digital technologies and innovations in shortening the way and time for the Maghreb region to reach and accelerate sustainable development. In the study, we concluded that the Industrial Revolution is a strategic choice to build a diversified, strong, sustainable and inclusive economy, and the adoption takes place in three phases. Through a SWOT analysis, it was found that the Maghreb has a real opportunity for diversification and sustainability by taking advantage of Fourth Industrial Revolution
The Fourth Industrial Revolution as a mechanism to drive and promote economic diversification for comprehensive sustainable development in the Maghreb
مقال
Keywords: التنويع الاقتصادي، التنمية المستدامة، الثورة الصناعية الرابعة، الابتكار الرقمي، منطقة المغرب العربي; sustainable development, Fourth industrial revolution, digital innovation, the Maghreb region